A relation of dominance for the bicriterion bus routing problem - Widuch, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
A bicriterion bus routing (BBR) problem is described and analysed. The objective is to find a route from the start stop to the final stop minimizing the time and the cost of travel simultaneously. Additionally, the time of starting travel at the start stop is given. The BBR problem can be resolved using methods of graph theory. It comes down to resolving a bicriterion shortest path (BSP) problem in a multigraph with variable weights.
Keywords: multicriteria optimization; set of non-dominated solutions; bicriterion shortest path problem; variable weights; label correcting algorithm; transportation problem